From fear and guilt: negative perceptions of Ashley Madison users. Issue 1 (3rd April 2017) - Hackathorn, Jana; Daniels, Jordan; Ashdown, Brien K.; Rife, Sean
ABSTRACT: A common cultural norm in committed relationships is that of sexual exclusiveness. When this norm is violated, those involved are often perceived negatively. Recently, a website facilitating extradyadic relationships, AshleyMadison.com (AM), was hacked, and the personal information of the members was illegally disseminated. As a result of the large amount of accompanying media coverage, AM users have been negatively perceived and even openly mocked. The current study explored potential predictors for the negative perceptions (i.e. demonisation) of AM users using a large online sample. In a predominantly exploratory study, myriad variables were examined from both outside (e.g. just world belief) and inside the psychosexual (e.g. sociosexuality) literature. The findings indicate that the predictors of jealousy and sexual guilt both positively predict demonisation of AM users, above and beyond the other individual difference variables.